Unarten: Kleist und das Gesetz der Gattung - Schönbeck, Sebastian; Preuss, Matthias; Allerkamp, Andrea (transcript, 2019)
Of dogs, goblins, and teddy bears: A critical and naughty examination of the concept of genre around 1800.